Time Is Brain; Factors Influencing The Outcome of Missile Head Injuries In Conflict Zone - Hussain, Zahid; Qasmi, Shahzad Ahmed (Pakistan Armed Forces medical journal, 2025)
Objective: To analyze factors influencing the outcome in patients with missile head injuries sustained in the conflict zone, to help in developing a plan for treating and optimizing such patients. Study Design: Retrospective longitudinal study Place and Duration of Study: Neurosurgical unit Combined Military Hospital Peshawar, Pakistan from Jul 2015 to Jun 2018. Methodology: Over a period of three years 66 male patients met the criteria with a mean age of 28 yrs. The variables identified were mechanism of injury: blast or gunshot injury, glasgow coma score (GCS) on arrival, time to reach to neurosurgical facility, location of entry wound, presence of Polytrauma, Pupils status, CT scan findings, surgical treatment, retained foreign body, seizures, hydrocephalus, cerebrospinal fluid leak and glasgow outcome scale extended (GOS E) score of 1-8. Results: Out of 66 patients, 12 patients (18.2%) sustained bullet injuries and 54 (81.8%) sustained blast splinter injuries to head. There were 24 patients (36.4%) with GOS score of 1 (death), 4 patients (6.1%) with GOS score of 6 (moderate disability), 9 patients (13.6%) with GOS score of 7 (good recovery lower) and 29 patients (43.9%) with GOS score 8 (good recovery). Conclusion:  In time adequate triage and prompt optimisation of patients before and during the safe medical evacuation of penetrating head injuries in the austere environment of conflict zone will lead the efforts to save the survivables and will push the balance to many good outcomes